2017
DOI: 10.1007/s00264-016-3384-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of clavicle hook plate implantation with different hook angles in the acromioclavicular joint

Abstract: A clavicle hook plate with different hook angles may induce different biomechanical behaviors in the clavicle and acromion. Orthopedic surgeons must select a suitable clavicle hook plate based on the anatomical structure of each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 16 publications
2
42
0
Order By: Relevance
“…Hung et al also used FEA to investigate the impacts of different hook angles. They found that a larger hook angle of implant exerted a larger load on the acromion because the larger hook angle made the contact position between the hook plate and acromion more proximal [24]. This theory seemed to contradict the phenomenon we encountered.…”
Section: Type Selection Of Clavicular Hook Platementioning
confidence: 62%
“…Hung et al also used FEA to investigate the impacts of different hook angles. They found that a larger hook angle of implant exerted a larger load on the acromion because the larger hook angle made the contact position between the hook plate and acromion more proximal [24]. This theory seemed to contradict the phenomenon we encountered.…”
Section: Type Selection Of Clavicular Hook Platementioning
confidence: 62%
“…Subacromial osteolysis and rotator cuff injury caused by the hook are serious complications caused by clavicle hook plates, and there are many reports of these complications [1][2][3][4][5][6][7][8][9][10][11]. An inappropriate hook depth and incongruency between the hook and undersurface of the acromion have been reported as causes of subacromial osteolysis [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Virtual implantation analysis for measuring the loading force on the acromion and clavicle has been conducted. Hung et al [11]. Demonstrated that a larger hook angle produces more force on the acromion.…”
Section: Discussionmentioning
confidence: 99%